Certain Class of Analytic Functions with respect to Symmetric Points Defined by Q-Calculus - K. R. Karthikeyan; G. Murugusundaramoorthy; S. D. Purohit; D. L. Suthar (Journal of Mathematics)
In this study, we familiarise a novel class of Janowski-type star-like functions of complex order with regard to j,k-symmetric points based on quantum calculus by subordinating with pedal-shaped regions. We found integral representation theorem and conditions for starlikeness. Furthermore, with regard to j,k-symmetric points, we successfully obtained the coefficient bounds for functions in the newly specified class. We also quantified few applications as special cases which are new (or known).